Experimental investigation of plastic injection molding: Assessment of the effects of cavity pressure and mold temperature on the quality of the final products - ATAKÖK, GÜRCAN; KURT, MUSTAFA; GİRİT, OĞUZ; KAYNAK, YUSUF (ELSEVIER SCI LTD, 2009)
Today more than ever, the molding industry demands better product quality. The quality of molded parts is crucial with regard to their functional capacity, and hence a great deal of attention should be directed towards maintaining consistent tolerances and overall dimensions. As the demand for high quality final parts continues to increase, the controlling parameters of cavity pressure and mold temperature become ever more significant in the plastic injection molding process. Therefore, in this research, cavity pressure and mold surface temperature have been measured and recorded by pressure and temperature-pressure sensors using a Kistler CoMo 2869A injection-type apparatus. The influences of the measured factors on the quality of the final parts have been investigated experimentally. The results of this experimental study indicate that cavity pressure and mold temperature are the dominant factors determining the quality of the final product in plastic injection molding. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: PROCESSING CONDITIONS; SHRINKAGE; WARPAGE; DESIGN; PARTS